2017
DOI: 10.1073/pnas.1616783114
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphism linked to increased asthma and IBD risk alters gasdermin-B structure, a sulfatide and phosphoinositide binding protein

Abstract: The exact function of human gasdermin-B (GSDMB), which regulates differentiation and growth of epithelial cells, is yet to be elucidated. In human epidermal growth factor receptor 2 (HER2)-positive breast cancer, GSDMB gene amplification and protein overexpression indicate a poor response to HER2-targeted therapy. Genome-wide association studies revealed a correlation between GSDMB SNPs and an increased susceptibility to Crohn's disease, ulcerative colitis, and asthma. The N-and C-terminal domains of all gasde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
189
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(210 citation statements)
references
References 55 publications
7
189
0
Order By: Relevance
“…3D). GSDMB-416 P311S (proline to serine change at residue 311), which was suggested to affect GSDMB protein conformation 44 , induced similar cytotoxicity as the wild type protein (Fig. 3D), indicating that rs2305480 has little effect on the pyroptotic activity of GSDMB.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…3D). GSDMB-416 P311S (proline to serine change at residue 311), which was suggested to affect GSDMB protein conformation 44 , induced similar cytotoxicity as the wild type protein (Fig. 3D), indicating that rs2305480 has little effect on the pyroptotic activity of GSDMB.…”
Section: Resultsmentioning
confidence: 94%
“…Another study showed that the asthma risk allele (T) of rs11078928 was associated with increased expression of GSDMB transcripts 43 . More recently, Chao et al reported that several apoptotic executioner caspases can cleave the GSDMB protein 44 . In addition, Das et al showed that GSDMB is expressed in human airway epithelial cells and that GSDMB expression increases with severity of asthma 33 .…”
Section: Discussionmentioning
confidence: 99%
“…While one group did not observe significant expression of gasdermin B in the lung[49], another group did observe gasdermin B in the lung and implicated it in influencing expression of genes related to airway remodeling and hyper-responsiveness[53]. Furthermore, one disease-associated SNP causes an alteration in the conformational flexibility and surface charge of a region in the RD[54]. The GSDMB SNPs and the GSDMB region of chromosome 17q21 have been associated with several other immune diseases as well[5562].…”
Section: Gasdermin D Pores Are the Effectors Of Pyroptosismentioning
confidence: 99%
“…A recent report shows that gasdermin B can be cleaved by caspase-3, -6, and -7 within the PFD[54], similar to PFD cleavage of gasdermin D[12]. Thus, both gasdermin B and gasdermin D may be inactivated during apoptosis to prevent pyroptosis after caspase-3 activates (although this idea is must be reconciled with caspase-3 activating gasdermin E, see below).…”
Section: Gasdermin D Pores Are the Effectors Of Pyroptosismentioning
confidence: 99%
“…However, because of linkage disequilibrium within the genome SNPs the challenge for the large‐scale genome sequencing is to reveal the disease causative SNPs. The structural studies of GSDMB_C were undertaken to provide insights into possible mechanisms that the SNPs may contribute to disease risk …”
Section: Resultsmentioning
confidence: 99%